Consider an economy populated by two types of infinitely lived consumers, odd and even. There is mass one of each type of consumer. There is a single good in the economy. The economy starts at $t = 0$. Odd agents have an endowment sequence $$e^0=\{3,1,3,1...\}$$ and even agents have $$e^0=\{1,3,1,3...\}$$ The preferences of both types of agents are described by the utility function $$U ( c ) =\sum\beta log\ c_t$$.

I need to compute the price and allocations. What I've done so far:

$$\max\sum\beta log\ c_t \ s.t \sum p_tc_t^i=\sum p_te_t^i$$ and market clear $c_t^1+c_t^2\leq e_t$

$$L=\sum\beta log\ c_t-\lambda^i(\sum p_tc_t^i-\sum p_te_t^i)$$ and gotten the focs: $\frac{\beta^t}{c-t^i}=\lambda^ip_t$. Guessing that $p_t = \beta_t$ I get that the consumption allocations of both agents are constant. I denote them by $c^1$ and $c^2$. Using this information in the budget constraints, I find: $$c^i\sum\beta^t=\sum p_te_t^i$$. Here is where I'm stuck. I know that we are supposed to use the geometric sequence but I am not sure. Is $c^1=\frac{1}{1+\beta}?$

  • $\begingroup$ Your budget constraint is ambiguous. Why is $\lambda$ indexed by $i$ (I guess $i$ is the good?) Is the sum $\Sigma$ over goods or over periods? Is there saving borrowing? $\endgroup$
    – tdm
    Commented Nov 10, 2021 at 11:29
  • $\begingroup$ $i$ is the individual I guess because it is stated that there is only one good in the economy and the sum is over periods. I don't think we need to consider saving or borrowing. It is just a simple endowment economy asking for eq. prices and allocations $\endgroup$ Commented Nov 10, 2021 at 14:14

1 Answer 1


Let's take for granted that $\sum_t p_t e_t^i$ is finite.

The first order conditions give: $$ \frac{\beta^t}{c_t^i} = \lambda^i p_t $$ This gives: $$ c_t^i = \frac{1}{\lambda^i}\frac{\beta^t}{p_t} \tag{1} $$ If we stubstitute into the budget constraint, we obtain: $$ \begin{align*} &\sum_t \frac{1}{\lambda^i} \beta^t = \sum_t p_t e_t^i,\\ \to &\frac{1}{\lambda^i} \sum_t \beta^t = \sum_t p_t e_t^i,\\ \to &\frac{1}{\lambda^i} \frac{\beta}{1 - \beta} = \sum_t p_t e_t^i,\\ \to &\frac{1}{\lambda^i} = \frac{(1-\beta)}{\beta}\sum_t p_t e_t^i. \end{align*} $$ Substituting back into $(1)$ gives for time period $v$: $$ c_v^i = \frac{(1-\beta)}{\beta} \frac{\beta^v}{p_v} \sum_t p_t e_t^i \tag{2} $$

Equilibrium on the market at every period $v$ gives: $$ \begin{align*} &c_v^1 + c_v^2 = 4,\\ \to &\frac{(1 - \beta)}{\beta} \frac{\beta^v}{p_v} \sum_t p_t (e_t^1 + e^t_2) = 4,\\ \to &\frac{(1 - \beta)}{\beta} \frac{\beta^v}{p_v} \sum_t p_t = 1 \end{align*} $$ This must hold for every $v$, so $p_v = \beta^v$ is a solution here.

Then we can compute the consumption of individual 1 in period $v$ as follows: $$ \begin{align*} c_v^1 &= \frac{(1-\beta)}{\beta}\sum_t p_t e_t^i,\\ &= \frac{(1-\beta)}{\beta}\left[\sum_{t \text{ odd}} \beta^t 3 + \sum_{t \text{ even}} \beta^t \right],\\ &= \frac{(1-\beta)}{\beta} \left[ \frac{3 \beta}{1 - \beta^2} + \frac{\beta^2}{1 - \beta^2}\right],\\ &= \frac{(1 - \beta)}{\beta} \frac{ 3 \beta + \beta^2}{1 - \beta^2},\\ &= \frac{(1 - \beta)}{\beta} \frac{(3 + \beta) \beta}{(1-\beta)(1+\beta)},\\ &= \frac{3 + \beta}{1 + \beta}. \end{align*} $$

We have that $c_v^2$ will be equal to $\dfrac{1 + 3 \beta}{1 + \beta}$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.